PENINGKATAN PERILAKU PROSOSIAL MELALUI PERMAINAN GALAH HADANG PADA ANAK USIA 5-6 TAHUN - Samsiar, Agus; Syukri, M; Halida, Halida (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThis research is based on the background of prosocial behavior based on data from the assessment of 15 children in PKK PAUD, Paritmayor Village, East Pontianak Subdistrict consisting of 6 women and 9 men, some of whom often play alone do not want to be friends with others, do not want to cooperate, not helping each other and not behaving honestly, therefore, the researcher focused this research on the efforts of teachers to improve prosocial behavior through the method of playing Galah Hadang in children aged 5-6 years in PKK PAUD Paritmayor Village, East Pontianak Subdistrict. class with descriptive method. Research subjects were 1 teacher and 15 children. Based on the results of research conducted and through the results obtained after data analysis was held that 1) planning learning in improving prosocial behavior through the method of playing Galah Hadang in children aged 5-6 years can categorized as "good". 2) The implementation of learning in improving prosocial behavior through the method of playing Galah Hadang in children aged 5-6 years can be categorized as "good". 3) Improvement of prosocial behavior through the method of playing Galah Hadang for children aged 5-6 years with the indicators being the target of assessment, namely: children can help each other among friends, can cooperate, children can share feelings, and children can behave honestlyÂ Keyword :Prosocial Behavior, Galah Hadang Play Method